Changes in the Ice-Front Position and Surface Elevation of Glaciar Pío XI, an Advancing Calving Glacier in the Southern Patagonia Icefield, From 2000–2018 - Hata, Shuntaro; Sugiyama, Shin (Frontiers in Earth Science, 2021)
Glaciar Pío XI has advanced and thickened over the past several decades in contrast to the generally retreating and thinning trends seen in other glaciers in the Southern Patagonia Icefield (SPI). To quantify recent changes in ice-front positions and glacier surface elevation over the ablation area of Glaciar Pío XI, we analyzed satellite data acquired from 2000 to 2018. Two major glacier termini, and most of the small outlet glaciers, showed advancing trends, including the largest advance (1400 m), observed at the southern terminus during the study period. Surface elevation increased by 37.3±0.4 m as a mean over the study area, and the rate of the increase accelerated by 135±10% from Period 1 (2000–2007) to Period 2 (2007–2017/18). Elevation change during Period 1 was only slightly positive except for extraordinary thickening ( 20 m a−1) observed near the southern terminus and one of the outlet glacier fronts, whereas significant thickening ( 2.7 m a−1) occurred over the entire ablation area during Period 2. Satellite imagery showed an emergence of sedimentary mounds in front of the southern terminus, suggesting that reduction in frontal ablation and increasingly compressive flow regime are the main drivers of the recent rapid thickening and advance. Most likely, the influence of the sediment deposition on the southern terminus subsequently propagated to the northern terminus and upper reaches of the glacier. The rate of ice mass increase during the study period was 0.48±0.03 Gt a−1, which corresponds to 4% of the total mass loss from the SPI from 2000 to 2015/16.